Circadian blood pressure variation in transgenic hypertensive rats - Lemmer, Björn; Mattes, Andreas; Böhm, Manfred; Ganten, Detlev (Hypertension, 1993)
Automatic, around-the-clock blood pressure measurements have increased our understanding of hypertension in humans. Patients with essential hypertension display patterns similar to those observed in normotensive subjects, whereas those with secondary hypertension frequently show abnormal circadian rhythms characterized by a failure to reduce blood pressure at night. We have modeled this situation in rats. Normotensive Wistar-Kyoto and Sprague-Dawley rats, spontaneously hypertensive rats, and rats made hypertensive by transgenic implantation of the mouse salivary gland renin gene (TGR[mRen-2]27) underwent chronic implantation of a device that telemetrically monitored their blood pressures, heart rates, and motor activities. In either normotensive or hypertensive rats, motor activity peaked during the dark phase, indicating that animals from all strains were nocturnal. In both normotensive and spontaneously hypertensive rats, the 24-hour blood pressure and heart rate profiles showed peak values during the rats' active phase at night, ie, between midnight and 3 AM. In the transgenic rats, on the other hand, blood pressure values were at maximum during the day around noon, when the rats were in their resting phase. The heart rate of the transgenic rats nevertheless still peaked around midnight. These data suggest that normotensive rats and those with primary and secondary hypertension display circadian rhythms of blood pressure and heart rate analogous to those observed in normotensive and primary or secondary hypertensive humans, respectively. The TGR(mRen-2)27 strain may be a useful model with which to investigate the mechanisms responsible for alterations in circadian rhythms of blood pressure and heart rate in forms of secondary hypertension.